Avaliação bioquímica-fisiológica de clones de batata em relação ao alumínio - Tabaldi, Luciane Almeri (2008)
Aluminum (Al) is the most abundant metal in the earth s crust, affecting thegrowth and development of plants. The objective of this work was to investigate and compare biochemical and physiological responses of potato clones, Macaca, SMIC148-A, Dakota Rose and Solanum microdontum, exposed to 0, 50, 100, 150 and 200 mg Al L-1 in nutrient solution (pH 4.0). After 7 days, Al content in roots was on average 3.9, 2.8, 3.6, and 3.7 fold greater than in shoot, in Macaca, S. microdontum, SMIC148-A and Dakota Rose clones, respectively. Based on the relative root growth, the S. microdontum and SMIC148-A were considered Al-tolerant while Macaca and Dakota Rose were considered Al-sensitive. Inhibition in shoot growth was observed only in Macaca clone. After 7 d of Al exposure, several biochemical parameters were affected, mainly in Al-sensitive clones, such as increased H2O2 concentration, catalase (CAT) activity and lipid peroxidation, and decreased chlorophyll and carotenoid content. In addition, zinc (Zn), manganese (Mn), iron (Fe) and copper (Cu) concentrations were higher in roots than in shoot of all potato clones tested. An increase in the concentration of most of the micronutrients analyzed was observed only in S. microdontum, while a decrease was observed in Macaca, SMIC148-A and Dakota Rose. Macaca, SMIC148-A, Dakota Rose and S. microdontum were grown in vitro, in hydroponics or in greenhouse to evaluate the effect of Al on the in vitro activity of acid phosphatases (APases). In plantlets grown in vitro, root APases were inhibited by Al in all clones, while shoot APases were inhibited by Al in S. microdontum and Dakota Rose and increased in Macaca at all Al levels. In plantlets grown in hydroponics, root APases increased in Macaca at 50 mg L-1, but decreased at all Al levels in S. microdontum. In greenhouse plantlets, root APases were reduced at 200 mg L-1 in S. microdontum and SMIC148- A, and at 100, 150 and 200 mg L-1 in Dakota Rose. Shoot APases were reduced in Macaca and SMIC148-A. Conversely, in Dakota Rose, APases increased at 50 and 100 mg L-1. Macaca (Al-sensitive) and SMIC148-A (Al-tolerant) clones were utilized in another experiment with the objective of evaluating whether the oxidative stress caused by Al is an early symptom than can trigger root growth inhibition. At 24, 72, 120 and 168 hours after Al addition, root growth inhibition and lipid peroxidation was observed only for the Al-sensitive clone. In the Al-tolerant clone, there was always at least one component of the antioxidant system protecting the plant against Al stress, which did not occur in the Al-sensitive clone. With the objective of checking whether Al oxidative stress differs in potato clones, Macaca (Al-sensitive) and SMIC148-A (Altolerant), which present distinct degrees of Al- avoidance, were cultivated in a splitroot system for 10 days with five treatments of varying concentrations and locations of Al. At 200 mg Al L-1, a significant decrease in chlorophyll concentration and increase in protein oxidation was observed only for Macaca. At 200 mg L-1 supplied to half of the root system, shoot H2O2 concentration was lower than that with both root halves treated by 100 mg L-1. Shoot lipid peroxidation in Macaca increased with increasing Al supply. In SMIC148-A, plants treated with 100 and 200 mg Al L-1 in only one root half showed lower shoot lipid peroxidation. The 200 half of 0/200 plants presented significantly greater lipid peroxidation than the half untreated by Al, mainly in Macaca. At 100 mg Al L-1 supplied to both root halves, Macaca showed an inefficient tolerance response, based on CAT activity, protein oxidation, lipid peroxidation, H2O2 concentration and APase activity. These results show that SMIC148-A, even though presenting lower Al-avoidance than Macaca, showed a stronger local and systemic antioxidant response to Al supply. Therefore, potato clones differed in their expression of antioxidant responses in terms of amount and type, suggesting that oxidative stress is an important mechanism for Al toxicity, mainly in Al-sensitive clones. This toxicity depends not only on Al availability but also on the clone and the growth system. In addition, it was observed that the adverse effects of Al do not disappear when part of the root system is not in contact with Al, mainly in the Al-sensitive clone.